Mouse t-complex protein 11 is important for progressive motility in sperm. Issue 4 (14th December 2019) - Castaneda, Julio M; Miyata, Haruhiko; Archambeault, Denise R; Satouh, Yuhkoh; Yu, Zhifeng; Ikawa, Masahito; Matzuk, Martin M
Abstract: The t -complex is defined as naturally occurring variants of the proximal third of mouse chromosome 17 and has been studied by mouse geneticists for decades. This region contains many genes involved in processes from embryogenesis to sperm function. One such gene, t-complex protein 11 ( Tcp11 ), was identified as a testis-specific gene whose protein is present in elongating spermatids. Later work on Tcp11 localized TCP11 to the sperm surface and acrosome cap and implicated TCP11 as important for sperm capacitation through the cyclic AMP/Protein Kinase A pathway. Here, we show that TCP11 is cytoplasmically localized to elongating spermatids and absent from sperm. In the absence of Tcp11, male mice have severely reduced fertility due to a significant decrease in progressively motile sperm; however, Tcp11 -null sperm continues to undergo tyrosine phosphorylation, a hallmark of capacitation. Interestingly, null sperm displays reduced PKA activity, consistent with previous reports. Our work demonstrates that TCP11 functions in elongated spermatids to confer proper motility in mature sperm. Abstract : T-complex protein 11, Tcp11, encodes a cytoplasmic protein expressed in the late stages of spermiogenesis that is important for sperm motility.